Analysis of Risk Factors Associated with Rabies Cases in South Timor Tengah Regency, East Nusa Tenggara, Indonesia - Lucitania Floreca Mokos; Setro Sri Rahardjo; Bhisma Murti; Yulia Lanti Retno Dewi; Nur Hafidha Hikmayani (Journal of Epidemiology and Public Health, 2025)
Background: Rabies is a zoonotic infectious disease that can be directly transmitted to humans and is fatal, leading to death in South Timor Tengah Regency. Rabies has been officially declared an outbreak in this region. This study aimed to analyze the effects of selected risk factors on rabies cases in South Timor Tengah Regency, East Nusa Tenggara Province, Indonesia. Subjects and Method: This study used primary data and employed an analytic observational design with a case–control approach. A total of 200 participants were included, consisting of 100 rabies cases and 100 controls, drawn from a population of 4,749 cases and controls using random sampling across 32 subdistricts in South Timor Tengah Regency. The dependent variable was rabies case status. The independent variables included community knowledge, history of contact with dogs, vaccination status of pet dogs, age, sex, stray dog bites, and stray dog population density. Data were collected using a questionnaire that had been tested for validity and reliability. Path analysis was conducted using STATA version 13. Results: The study found significant associations between rabies cases and community knowledge (OR= 0.06; 95% CI= 0.03–0.16; p < 0.001), stray dog population density (OR= 2.72; 95% CI= 1.30–5.70; p= 0.008), stray dog bites (OR = 4.59; 95% CI= 1.97–10.69; p < 0.001), age (OR= 0.97; 95% CI= 0.95–0.99; p= 0.008), and sex (OR= 0.33; 95% CI= 0.16–0.71; p = 0.005). In contrast, history of contact with dogs (OR= 1.30; 95% CI= 0.62–2.71; p= 0.487), vaccination of pet dogs (OR= 0.89; 95% CI= 0.37–2.13; p = 0.796), and educational level (OR = 1.31; 95% CI= 0.54–3.15; p= 0.553) were not statistically significant. Conclusion: High stray dog population density and stray dog bites increase the risk of rabies, while higher community knowledge, female sex, and age ≥35 years serve as protective factors against rabies in the population of South Timor Tengah Regency.